Industrial policy: state stimulation of innovative activity of enterprises - A. A. Ermolina; D. A. Stepanenko (Омский научный вестник: Серия "Общество. История. Современность")
The study is devoted to the development of methods of state stimulation of innovative activity of industrial enterprises. The aim is to develop proposals for improving state policy of increasing the innovative activity of industrial organizations, their systematization and the creation of a classification of methods. The article examines the regulatory framework for the implementation of innovative activities, analyzes the indicators characterizing the innovative activity of enterprises, identifies the obstacles to their innovative development, analyzes the effectiveness of the current industrial state policy and trends in its change. Conclusions are drawn about the low innovative activity of industrial enterprises due to the ineffectiveness of industrial policy and government incentives. We proposed the new methods of state stimulation of innovative activity and we made their classification. The implementation of the developed approaches and methods will increase the innovative activity of enterprises and the competitiveness of the national economy